Analysis of KUCA measurements by the reactivity monitoring MAρTA method. (March 2017) - Dulla, Sandra; Hoh, Siew Sin; Marana, Gaia; Nervo, Marta; Ravetto, Piero; Pyeon, Cheol Ho
Highlights: The MA ρ TA method for reactivity monitoring is applied to experimental data. Pulsed experiments performed in the KUCA facility are considered. The scope of the work is to validate the method using real experimental data. A thorough analysis of statistical uncertainty is carried out. Results are compared with the classic area ratio method, proving consistency. Abstract: A recently developed method for the continuous reactivity monitoring in nuclear reactors and in subcritical source-driven systems is applied for the interpretation of flux measurements carried out in the KUCA facility. The scope of the work is to validate the method using real experimental data. The method is based on general mathematical properties of the differential equations constituting the point kinetic model. Several pulsed experiments performed in different system configurations and using different source target materials are analysed. The results are compared with the classic area ratio method. A good agreement is obtained when the space-energy transient following the source shut-down dies out and when the system sets on a point-like evolution. The results prove the suitability of the proposed method for application to the reactivity monitoring of source-driven systems.